Production of IgY Specific Antibody Against Entero Pathogenic Escherichia coli (EPEC) in Egg Yolk - I Wayan Teguh Wibawan; Fachriyan H. Pasaribu; Rudi Rawendra (Universitas Syiah Kuala, 2010)
Antibody to Enteropathogenic Eschericia coli (EPEC) K1.1. can be produced in egg yolk by the application of inactivated bacterial cells intravenously in layer chicken. The presence of specific antibody in sera and egg can bedetected with immunodiffusion techniques (Agar Gel Precipitation Test/AGPT), expressed by the occurrence of specific precipitation reaction between antibody and homolog antigen and no cross reaction of this antibody with antigen of Salmonella sp. and Klebsiella sp. The presence of specific antibody previously can be detected in sera, then 1 week after this the antibody start to be able be detected in egg yolk. The antibody is still present in sera as well as in egg yolk in large amount for 7 weeks and decrease significantly in the 8th week. This results indicated that theegg can be used in the producing specific antibody in the large quantity.